Rethinking the Lake History of Taylor Valley, Antarctica During the Ross Sea I Glaciation - Michael S. Stone; Peter T. Doran; Krista F. Myers (Geosciences)
The Ross Sea I glaciation, marked by the northward advance of the Ross Ice Sheet (RIS) in the Ross Sea, east Antarctica, corresponds with the last major expansion of the West Antarctic Ice Sheet during the last glacial period. During its advance, the RIS was grounded along the southern Victoria Land coast, completely blocking the mouths of several of the McMurdo Dry Valleys (MDVs). Several authors have proposed that very large paleolakes, proglacial to the RIS, existed in many of the MDVs. Studies of these large paleolakes have been key in the interpretation of the regional landscape, climate, hydrology, and glacier and ice sheet movements. By far the most studied of these large paleolakes is Glacial Lake Washburn (GLW) in Taylor Valley. Here, we present a comprehensive review of literature related to GLW, focusing on the waters supplying the paleolake, signatures of the paleolake itself, and signatures of past glacial movements that controlled the spatial extent of GLW. We find that while a valley-wide proglacial lake likely did exist in Taylor Valley during the early stages of the Ross Sea I glaciation, during later stages two isolated lakes occupied the eastern and western sections of the valley, confined by an expansion of local alpine glaciers. Lake levels above ~140 m asl were confined to western Taylor Valley, and major lake level changes were likely driven by RIS movements, with climate variables playing a more minor role. These results may have major implications for our understanding of the MDVs and the RIS during the Ross Sea I glaciation.